Performance of anti-CD19 chimeric antigen receptor T cells in genetically defined classes of chronic lymphocytic leukemia. Issue 1 (26th March 2020) - Mancikova, Veronika; Peschelova, Helena; Kozlova, Veronika; Ledererova, Aneta; Ladungova, Adriana; Verner, Jan; Loja, Tomas; Folber, Frantisek; Mayer, Jiri; Pospisilova, Sarka; Smida, Michal
Abstract : Background: While achieving prolonged remissions in other B cell-derived malignancies, chimeric antigen receptor (CAR) T cells still underperform when injected into patients with chronic lymphocytic leukemia (CLL). We studied the influence of genetics on CLL response to anti-CD19 CAR T-cell therapy. Methods: First, we studied 32 primary CLL samples composed of 26 immunoglobulin heavy-chain gene variable ( IGHV )-unmutated (9 ATM -mutated, 8 TP53 -mutated, and 9 without mutations in ATM, TP53, NOTCH1 or SF3B1 ) and 6 IGHV -mutated samples without mutations in the above-mentioned genes. Then, we mimicked the leukemic microenvironment in the primary cells by '2S stimulation' through interleukin-2 and nuclear factor kappa B. Finally, CRISPR/Cas9-generated ATM - knockout and TP53- knockout clones (four and seven, respectively) from CLL-derived cell lines MEC1 and HG3 were used. All these samples were exposed to CAR T cells. In vivo survival study in NSG mice using HG3 wild-type (WT), ATM - knockout or TP53- knockout cells was also performed. Results: Primary unstimulated CLL cells were specifically eliminated after >24 hours of coculture with CAR T cells. '2S' stimulated cells showed increased survival when exposed to CAR T cells compared with unstimulated ones, confirming the positive effect of this stimulation on CLL cells' in vitro fitness. After 96 hours of coculture, there was no difference in survival among the genetic classes. Finally, CAR T cells were specifically activated in vitro in the presence of target knockout cell lines as shown by the production of interferon-γ when compared with control (CTRL) T cells (p=0.0020), but there was no difference in knockout cells' survival. In vivo, CAR T cells prolonged the survival of mice injected with WT, TP53 -knockout and ATM -knockout HG3 tumor cells as compared with CTRL T cells (p=0.0485, 0.0204 and <0.0001, respectively). When compared with ATM -knockout, TP53 -knockout disease was associated with an earlier time of onset (p<0.0001), higher tumor burden (p=0.0002) and inefficient T-cell engraftment (p=0.0012). Conclusions: While in vitro no differences in survival of CLL cells of various genetic backgrounds were observed, CAR T cells showed a different effectiveness at eradicating tumor cells in vivo depending on the driver mutation. Early disease onset, high-tumor burden and inefficient T-cell engraftment, associated with TP53 -knockout tumors in our experimental setting, ultimately led to inferior performance of CAR T cells.